De tuin van Teirlinck - Vangrunderbeek, Dimitri; Herman Teirlinckhuis, Beersel (Beersel : Herman Teirlinckhuis Beersel, 2004)
D'Hondt, Lieve ; Lester, Gabriël ; Roberts, Perry ; Thirion, Dominique ; Thys, Harald ; Vangrunderbeek, Dimitri ; Voet, Heidi
Biog., ind. tent., gr. tent. p. 25-27
Publicatie n.a.v. de tentoonstelling "De tuin van Teirlinck" in het Herman Teirlinckhuis te Beersel, 08.05.2004 - 30.06.2004
boek